The influence of work overload, person-job fit, and work engagement on employee performance through job stress as a variable intervening in automotive companies - Deasy Rinayanti Pelealu (Institute of Computer Science (IOCS), 2023)
Internal factors that affect employee performance include employee quality and competence related to education, training, work ethic, motivation, and mental resilience that affect work stress thresholds, the suitability of employee characteristics with the field of work and the physical condition of employees. This study aims to examine the factors that affect employee performance to help companies evaluate work, especially in terms of work overload, person-job fit, and work engagement. The research uses quantitative methods with 100 employees from the Pontianak City automotive industry as subjects. The analysis of this study is a structural approach to the Equation Model (SEM) with the help of smart PLS. The workload variable has a significant positive effect on work stress, the person-job fit variable has a significant negative effect on work, the work engagement variable has a significant negative effect on work stress, the work overload variable has no effect on employee performance, and person-job fit variable has a significant positive effect on performance employees, there is a significant positive effect between work engagement variables on employee performance, a significant negative effect between work stress variables on employee performance, a significant negative effect between workload variables on employee performance mediated by work stress, a significant negative effect between person-job fit variables on employee performance is mediated by work stress. There is no influence between variables on employee performance.